A20/TNFAIP3 Increases ENOS Expression in an ERK5/KLF2-Dependent Manner to Support Endothelial Cell Health in the Face of Inflammation - Angolano, Cleide; Kaczmarek, Elzbieta; Essayagh, Sanah; Daniel, Soizic; Choi, Lynn Y.; Tung, Brian; Sauvage, Gabriel; Lee, Andy; Kipper, Franciele C.; Arvelo, Maria B.; Moll, Herwig P.; Ferran, Christiane (Frontiers in Cardiovascular Medicine, 2021)
Rationale. Decreased expression and activity of endothelial nitric oxide synthase (eNOS) in response to inflammatory and metabolic insults is the hallmark of endothelial cell (EC) dysfunction that preludes the development of atherosclerosis and hypertension. We previously reported the atheroprotective properties of the ubiquitin-editing and anti-inflammatory protein A20, AKA TNFAIP3, in part through interrupting nuclear factor-kappa B (NF-B) and interferon signaling in EC and protecting these cells from apoptosis. However, A20’s effect on eNOS expression and function remains unknown. In this study, we evaluated the impact of A20 overexpression or knockdown on eNOS expression in EC, at baseline and after tumor necrosis factor (TNF) treatment, used to mimic inflammation. Methods and Results. A20 overexpression in human coronary artery EC (HCAEC) significantly increased basal eNOS mRNA (qPCR) and protein (Western blot) levels and prevented their downregulation by TNF. Conversely, siRNA-induced A20 knockdown decreased eNOS mRNA levels, identifying A20 as a physiologic regulator of eNOS expression. By reporter assays, using deletion and point-mutants of the human eNOS promoter, and knockdown of eNOS transcriptional regulators, we demonstrated that A20-mediated increase of eNOS was transcriptional and relied on increased expression of the transcription factor Krüppel-like factor (KLF2), and upstream of KLF2, on activation of extracellular signal-regulated kinase 5 (ERK5). Accordingly, ERK5 knockdown or inhibition significantly abrogated A20’s ability to increase KLF2 and eNOS expression. In addition, A20 overexpression in HCAEC increased eNOS phosphorylation at Ser-1177, which is key for the function of this enzyme. Conclusions. This is the first report demonstrating that overexpression of A20 in EC increases eNOS transcription in an ERK5/KLF2-dependent manner and promotes eNOS activating phosphorylation. This effect withstands eNOS downregulation by TNF, preventing EC dysfunction in the face of inflammation. This novel function of A20 further qualifies its therapeutic promise to prevent/treat atherosclerosis.